(untitled) (Revista Brasileira de Contabilidade e Gestão, 2014)
The purpose of this study is to demonstrate software development and application for data analysis in order to provide new guidelines for its use in large amounts of unstructured text in management’s context. This project was based on a study about traveler engagement with hotels at a tourist destination through online reviews on travel planning websites. Data were automatically collected, pre-processed, categorized and disposed into dynamic and interactive visualizations in order to provide qualitative and quantitative analysis of the reviews. The results demonstrate how the categorization by themes and graphics can condense the information available in a specialized tourism social network (TripAdvisor).